Retelling the past, inspiring the future: Waffen-SS commemorations and the creation of a 'European' far-right counter-narrative. (19th October 2016) - Hurd, Madeleine; Werther, Steffen
ABSTRACT: Heinrich Himmler created the Waffen-SS in part as a multinational force, willing to fight for a New Europe based on Germanic blood. After the war, many international Waffen-SS units formed veterans' associations (VAs). Like other VAs, these provided veterans with the chance to engage in 'memory work' and to keep alive a sense of comradeship and of valiant sacrifice, as well as an emotional commitment to the fallen. Waffen-SS veterans were, however, alone in celebrating their 'sacrifices'. Others shunned them for their participation in atrocities. To defend themselves, they developed a counter-hegemonic Second World War narrative that presented the Waffen-SS as uniquely heroic 'European' volunteers' against Bolshevism. This counter-narrative, however, only gained resonance with the fall of the Berlin Wall. After 1989, in fact, veterans could seek out and establish sites of public commemoration, not in Western but in Eastern Europe. Hurd and Werther use veterans' journals and books to explore the redeployment of SS ideology in a revisionist version of history. They examine the resurrection of a mass Waffen-SS graveyard in East Ukraine as a telling case history, discussing, not least, the implications of a 'reconciliation' of the former German soldiers with both Ukrainian villagers and Red Army veterans. Finally, they explore the significance of the veterans' 'European' counter-history for a younger generation of neo-Nazis.